Techno-spiritual design model (TSDM): a case study of prayer practice among the elderly population / Juhaida Ismail - Ismail, Juhaida (2022)
There are wide ranges of interventions available to compensate the elderly with functional impairments that accompany aging, yet this research argues that most of the technology designers focused primarily on physical, emotional, and social needs of the elderly, and overlooked their spiritual needs. Besides, less attention is given to the approach of designing the applications that support spiritual needs. Hence, this study seeks to propose the use of technology to support the Islamic spirituality as the study context. Thus, Islamic perspective is needed for the technology assessment. However, there is no model proposed by Islamic scholars to direct the technological endeavor and set appropriate technological goals in Muslim societies. Hence, there is a need of a model for Muslims that is bound by the religious rulings. Accordingly, this study explores the techno-spirituality space through the development of the proposed aid, the Smart Prayer Mat. Three main studies were conducted, following the design science approach, with each having a different and specific aim. The first is qualitative and exploratory, aiming to understand the artefact context of use, design, and implication within the spiritual context. Hence, to attain a thorough understanding of the techno-spiritual context, key informant interviews were conducted with prominent Islamic scholars and a user experience expert. Thematic analysis was performed on the interview transcripts, and it shows significant themes emerged from the study context. The findings of the first study led us to draw a conceptual model of techno spiritual that can be used as design informant of designing techno-spiritual artefacts. The second study aims to design an artefact, which then be evaluated by our targeted end users, the elderly. The third study aims to verify the proposed model among the users and the experts. User evaluation is achieved by the mean of user testing where the data were collected based on sensor data and post-experience interview. 20 elderly responses were used in the data analysis. The instrument for artefact evaluation was constructed, which contains two main dimensions: technological and Islamic spiritual context. For expert evaluation, descriptive and qualitative analysis were conducted in gaining a deeper understanding of each expert, including their opinions and perspectives of the proposed model. The results from both the analyses enable us to construct the Techno-Spiritual Design Model (TSDM), comprising three constructs; (1) permissible, (2) non-intrusive and (3) evoke spiritual experience. This model will serve as design informant, which regulates and facilitates the design of Muslims’ techno-spiritual application. Accordingly, it will benefit future researchers and designers toward better development of techno-spiritual artefact